ISTOTA I SENS AKTU INTRONIZACJIJEZUSA CHRYSTUSA – PRÓBA INTERPRETACJI = The Nature and Sense of Enthronement of Jesus Christ – An Attempt at an Interpretation - Perka, Paweł (Studia religiologica, 2009)
The article aims to explain the rite of enthronement of Jesus the King using terminology borrowed from, among others, the anthropological inquiries by Roy A. Rappaport and from a sociological analysis of religion made by Peter L. Berger. Emphasis is placed on explaining the adaptive role of the ritual in establishing and maintaining a convention which offers to individuals a coherent narrative system to organize their perceptions. On the example of the enthronement ritual of Jesus the King, created by the Polish mystic Rozalia Celakówna, the author tries to show how performative acts of speech form a distinct space in social life.